An alternative method for the calculation of Chandrasekhar's H-function and its derivative. (September 2021) - Anlı, Fikret; Öztürk, Hakan
Highlights: A new analytical approach is developed to compute Chandrasekhar's H-function and its derivative. A constraint is constructed for the numerical solution. New results differ from published data by less than 0.03 % in average. Results are more accurate for lower single scattering albedo values. Abstract: In this paper, a new approach using shifted Legendre polynomials has been applied for the numerical solution of the nonlinear integral equation for the Chandrasekhar H-function for isotropic scattering. This new analytical approach with its easily executable equations brought the nonlinear equation to a numerically computable form. Our numerical results show good agreement with those reported in existing literature with a difference between 0.0009 % and 0.11 %.